PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Arif Haryadi; Roza Yulida; Rosnita ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to know the guidance role of palm oil plantations in the rock. To know the empowerment of the oil palm growers self-help patterns in the rock.Conduct an analysis of the achievement of education is seen from better farming, better business, and better livingAnalyze the influence of the role of education forem power mentan dem power mentin fluenceon the destination extension in Bukit Batu subdistrict. The data collection method using survey methods. Type making purposive sampling of respondents with oil palm farmers in the non-pattern excl. the rock. Data were analyzed by descriptive analysis using a Likertscale, SPSS17, and Amos. The results showed1). The roleof extensionof theactivities ofoil palm cultivationin the district of Bukit Batu